Toll Road Tariff Increase Policy Against Public Interest - Ahmad Munir; M. Najib Alif; Mohammad Ihyaul Ulum (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2023)
A significant increase in toll road fares will be implemented on the Surabaya-Gresik Toll Road in 2022. The policy of increasing the tariff for the Surabaya-Gresik toll road is carried out when inflation is high and there is the COVID-19 pandemic. This study uses a normative research method with a statutory approach and a conceptual approach related to toll roads and the concept of public interest in the imposition of toll road tariffs. No research has been conducted from the point of view of the public's interest regarding the policy of increasing toll road fares. This study aims to analyze the policy of increasing toll road fares against the public's interest. The results of this study show that the imposition of toll road tariffs is a source of state revenue that does not come from taxes. In addition, the construction of toll roads is in the public's interest. However, the increase in toll road fares when inflation is high and there is a COVID-19 pandemic cannot be justified because the burden on society will increase. The toll road tariff adjustment should be waived or reduced if investment feasibility has been obtained and the minimum service standards are not fulfilled and/or reduced for economic development.